PELAYANAN PERIZINAN TANDA DAFTAR PERUSAHAAN PADA DINAS PERINDUSTRIAN, PERDAGANGAN, KOPERASI DAN USAHA KECIL MENENGAH KABUPATEN OGAN KOMERING ULU SUMATERA SELATAN - Raniasa Putra (Indonesian Journal of Dialectics, 2012)
These research problems are the public do not register their company registration card. The statement of this research can be formulated as : the publishing service of company registration card in Departement of Industry, Trading, Cooperative and Small and Medium Enterpries in Ogan Komering Ulu Regency South Sumatera is not good. The quetion of this research can be formulated as : How is the way of the licensing service of company registration card in Departement of Industry, Trading, Cooperative and Small and Medium Enterpries in Ogan Komering Ulu Regency South Sumatera. The aim of this research is to obtain new concept on administration study, particularly regarding the public service. Therefore this research is based on responsiveness, responsibility dan accountability concepts as guidance theory. The method of this studi is descriptive analysis by using qualitative approachment. Through a qualitative approach. Researcher as the main instrument collected, processed,analyzed and verified any data from key informed, documents and field observation related to research problem. The result ofthis study showed that the licensing service in Departement of Industry, Trading, Cooperative and Small and Medium Enterpries in Ogan Komering Ulu Regency South Sumatera is not good, due not only because it has not completely based on responsiveness, responsibility and accountability concepts, but also because of the neglect of equity concept.